Aging related decreases in NM myosin expression and contractility in a resistance vessel - Han, Young Soo; Bandi, Rishiraj; Fogarty, Matthew J.; Sieck, Gary C.; Brozovich, Frank V. (Frontiers in Physiology, 2024)
Vasodilatation in response to NO is a fundamental response of the vasculature, and during aging, the vasculature is characterized by an increase in stiffness and decrease in sensitivity to NO mediated vasodilatation. Vascular tone is regulated by the activation of smooth muscle and nonmuscle (NM) myosin, which are regulated by the activities of myosin light chain kinase (MLCK) and MLC phosphatase. MLC phosphatase is a trimeric enzyme with a catalytic subunit, myosin targeting subunit (MYPT1) and 20kDa subunit of unknown function. Alternative mRNA splicing produces LZ+/LZ-MYPT1 isoforms and the relative expression of LZ+/LZ-MYPT1 determines the sensitivity to NO mediated vasodilatation. This study tested the hypothesis that aging is associated with changes in LZ+ MYPT1 and NM myosin expression, which alter vascular reactivity. We determined MYPT1 and NM myosin expression, force and the sensitivity of both endothelial dependent and endothelial independent relaxation in tertiary mesenteric arteries of young (6mo) and elderly (24mo) Fischer344 rats. Our data demonstrate that aging is associated with a decrease in both the expression of NM myosin and force, but LZ+ MYPT expression and the sensitivity to both endothelial dependent and independent vasodilatation did not change. Further, smooth muscle cell hypertrophy increases the thickness of the medial layer of smooth muscle with aging. Thus, the reduction of NM myosin may represent an aging associated compensatory mechanism to normalize the stiffness of resistance vessels in response to the increase in media thickness observed during aging.